The Brainliest Answer!

This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We have to rationalize the denominator by multiplying with its conjugate irrational expression.  So we multiply the numerator and denominator with  7 - √3 on the LHS.

\frac{5 + 2 \sqrt3}{7+\sqrt3}=a-\sqrt3 b\\\\\frac{(5 + 2 \sqrt3)(7-\sqrt3)}{(7+\sqrt3)(7-\sqrt3)}=a-\sqrt3 b\\\\\frac{35-2*3+9\sqrt3}{7^2-3}=a-b\sqrt3\\\\a=\frac{29}{46}\\\\b=\frac{-9}{46}

That is the answer.

3 5 3